Assessing Forest Fire Susceptibility in Bhojpur District, Nepal: A GIS-AHP Integrated Approach - Tiwari, Saksham; Chalise, Prashant; Adhikari, Prashanta; Gautam, Jeetendra (Journal of Agriculture and Forestry University, 2026)
Forest fires have been a major threat to forest ecosystems, as well as human populations, depending on forest. Bhojpur district, which has rich biodiversity and extensive forest cover, faces similar recurrent fires threats during dry season causing ecological and socio-economic losses. However, no detailed fire risk zonation map exists, limiting proactive management. Therefore, this study was required to identify and map areas of varying fire susceptibility to support risk mitigation. A Geographic Information Systems and the Analytic Hierarchy Process was employed to model potential fire risk map through the integration of eleven geospatial variables: Land Use Land Cover, Normalised Difference Vegetation Index, Land Surface Temperature, Slope, Aspect, Elevation, Precipitation, Wind Speed, Topographic Wetness Index, Distance to Roads, and Distance to Population. The consistency ratio was 0.08, and the Area Under the Curve was 0.826, indicating valid and acceptable structural model. 20.72% of the land was classified as high risk, 78.93% as moderate risk, and a tiny portion was classified as extreme or low risk. This map is considered an essential tool for authorities in assessing, analyzing, and formulating risk mitigation, as well as forest ecosystem resilience management strategies.